Trends in the scientific production on aquatic microhabitats phytotelmata: a scientometric study - Teixeira, Ana Paula; Silva, Paulo Fernandes Roges Souza; Souza, João Paulo Francisco de; Alves, Natália Lopes; Guimarães, Ariane; Carneiro, Fernanda Melo (Acta scientiarum. Biological sciences, 2018)
We performed a scientometry to validate trends in the scientific production on phytotelmata and the importance of these microenvironments in the maintenance of biodiversity. We searched for articles in the Web of Science and looked at publications from 1987 to 2016. We collected years of publication, surveyed organisms, countries where the surveys took place, plants that accumulate phytotelmata, scientific journals that publish more about the topic and their respective IFs (Impact Factor) and the keywords of each article. We built a heatmap using the most frequent keywords in the studies, to investigate the topics studied over the years. We have found 293 publications, increasing over the years. Insects, anurans and crustaceans were the most studied organisms. The most studied plant families were Bromeliaceae, Poaceae and Apiaceae. The published studies analized were carried out mainly in Brazil, Argentina and Peru. The most published journals on the subject are: Zootaxa, Hydrobiologia, Biotropica and Journal of Natural History. Some main global concerns such as climate change, habitat fragmentation has gained the attention of the phytotelmata studies in the recent years. The results contribute to the knowledge about phytotelmata accumulated biodiversity and research trends.